Venice's secret service - Iordanou, Ioanna ca. 20./21. Jh (Oxford scholarship online, 2019)
Ioanna Iordanou traces the remarkable development of Venetian intelligence in the city-state system of Northern Italy, contesting that early-modern Venice was home of the world's first centrally-organized state intelligence service, setting a framework that has been instrumental in the creation of modern intelligence